2021
DOI: 10.1001/jamanetworkopen.2021.5845
|View full text |Cite
|
Sign up to set email alerts
|

Association of Dual LRRK2 G2019S and GBA Variations With Parkinson Disease Progression

Abstract: IMPORTANCE Despite a hypothesis that harboring a leucine-rich repeat kinase 2(LRRK2) G2019S variation and a glucocerebrosidase (GBA) variant would have a combined deleterious association with disease pathogenesis, milder clinical phenotypes have been reported in dual LRRK2 and GBA variations Parkinson disease (PD) than in GBA variation PD alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 47 publications
4
34
0
Order By: Relevance
“…A study with a cohort of 236 participants showed that the LRRK2 mutation together with GBA rescued from further mental degeneration [150]. Meanwhile, a recent study with a cohort of 1193 Ashkenazi Jewish population showed no differences between genotypes [151].…”
Section: Lrrk2mentioning
confidence: 99%
“…A study with a cohort of 236 participants showed that the LRRK2 mutation together with GBA rescued from further mental degeneration [150]. Meanwhile, a recent study with a cohort of 1193 Ashkenazi Jewish population showed no differences between genotypes [151].…”
Section: Lrrk2mentioning
confidence: 99%
“…It would be anticipated that having a mutation in both LRRK2 and GBA would have an added deleterious effect, as suggested by laboratory studies [ 146 , 147 ]. However, a recent longitudinal study of a large PD sample measuring progression using the Montreal Cognitive Assessment and Movement Disorders Society—Unified Parkinson Disease Rating Scale–Part III, showed that patients with both the p.G2019S mutation and GBA -PD had a slower rate of decline than those with GBA -PD alone, which was no different from LRRK2 -G2019S alone [ 148 ]. Similarly, a retrospective observational study of Ashkenazi Jewish patients revealed that patients with mutations in LRRK2 and GBA (described by the authors as “ GBA - LRRK2 -PD”) were less frequently affected by dementia, probable REM-behavior sleep disorder, and psychosis, compared to other groups ( GBA -PD, LRRK2 -PD, mutation-negative PD) [ 149 ].…”
Section: Dual Lrrk2 and Gba Mutation Carriersmentioning
confidence: 99%
“…In a larger study, 27 dual mutation patients (all with LRRK2 G2019S and a majority with mild GBA mutations) have significantly better motor function, lower rates of dementia and slower cognitive decline than both mild and severe GBA mutation carriers, again implying a modifying role of LRRK2 on motor and nonmotor phenotypes of patients with GBA mutations [ 94 ]. Combining data from multiple studies, Ortega and colleagues showed that GBA- PD (containing similar proportions of patients with mild and severe GBA mutation to the dual mutation group) have the fastest motor and cognitive decline compared with LRRK2 -PD, PD with dual mutations and iPD, while the latter three groups are similar on this aspect [ 95 ]. Data concerning the age of onset of LRRK2-GBA dual mutation carriers are conflicting.…”
Section: Dual Lrrk2-gba Mutations In Pd Patientsmentioning
confidence: 99%
“…Data concerning the age of onset of LRRK2-GBA dual mutation carriers are conflicting. Two studies reported that PD patients with LRRK2-GBA dual mutations were younger at first motor symptom onset than single mutation carriers [ 93 , 96 ], while no such differences were found in two other studies [ 94 , 95 ].…”
Section: Dual Lrrk2-gba Mutations In Pd Patientsmentioning
confidence: 99%